The Long-Term Consequences of a Golden Nest - Viola Angelini; Marco Bertoni; Guglielmo Weber (Institute of Labor Economics (IZA), 2020)
We study the role played by the standard of living during childhood on nest leaving. Using data from SHARE, we show empirically that individuals who grew up in a golden nest leave the parental home later and that education only partially mediates this effect. This relationship holds across different cultures, for both males and females, urban and rural residents. We then use a 3-period lifecycle model to show that this behaviour is consistent with standard assumptions on preferences and resources if earnings increase with age, and that habit-forming preferences reinforce the delaying effect of a golden nest on nest leaving.
Keywords: D15; J12; J13; J62; 330; nest leaving; socio-economic status; habit-forming preferences; intergenerational mobility; SHARE